STUDY OF E-SPORTS TOURISM POTENTIAL USING TRIPLE BOTTOM LINE ANALYSIS METHOD - Frans, Alfiano Johanes; Hery Sigit Cahyadi; Sugeng Hermanto (Politeknik Pariwisata NHI Bandung, 2022)
This study discusses the potential of the electronic sports industry in the tourism sector, especially in urban areas in Indonesia. In this case, the potential in question includes the potential for product components in the electronic sports event industry ecosystem, as well as the potential for industrial models in the aspect of sustainability. The method used in this study is a descriptive method with a qualitative approach, with the distribution of participants being all tourists from electronic sports events in urban areas in Indonesia. From the results of this study, it can be concluded that currently the electronic sports industry is growing rapidly in Indonesia and the world, this industry also indicates a positive influence on the development of the social, economic, and natural resources surrounding the industrial operating environment, so that it has the potential to become a sustainable tourism resource in the future. This study discusses the potential of the electronic sports industry in the tourism sector, especially in urban areas in Indonesia. In this case, the potential in question includes the potential for product components in the electronic sports event industry ecosystem, as well as the potential for industrial models in the aspect of sustainability. The method used in this study is a descriptive method with a qualitative approach, with the distribution of participants being all tourists from electronic sports events in urban areas in Indonesia. From the results of this study, it can be concluded that currently the electronic sports industry is growing rapidly in Indonesia and the world, this industry also indicates a positive influence on the development of the social, economic, and natural resources surrounding the industrial operating environment, so that it has the potential to become a sustainable tourism resource in the future